A systematic analysis and comparison of warfarin initiation strategies. Issue 10 (October 2016) - French, Benjamin; Wang, Le; Gage, Brian F.; Horenstein, Richard B.; Limdi, Nita A.; Kimmel, Stephen E.
Abstract : Objective: Randomized trials have reported inconsistent evidence on the effectiveness of algorithms that use genotypes to initiate warfarin therapy. The Clarification of Optimal Anticoagulation through Genetics (COAG) trial initiated therapy on the basis of predicted maintenance doses, with a pharmacogenetic-guided algorithm in one study group and a clinically guided algorithm in the other. The European Pharmacogenetics of Anticoagulant Therapy (EU-PACT) consortium initiated therapy on the basis of loading doses, with an algorithm-based prediction in one study group and a fixed-dose regimen in the other. To understand the differences between these trials, we compared the initial doses between alternative dosing algorithms (the pharmacogenetic-guided and clinically guided algorithms developed by Gage and colleagues and those developed by the International Warfarin Pharmacogenetics Consortium) and between the COAG and EU-PACT dose-initiation strategies. Methods: This was a secondary analysis of the COAG trial – a double-blind, randomized-controlled trial (2009–2013) – conducted at 18 clinical centers in the USA, which included 1010 adults initiating warfarin therapy, of whom 719 achieved maintenance dose. Results: Among COAG participants, the distribution of initial doses differed between algorithms, but showed similar prediction accuracy for maintenance dose. However, had the COAG trial implemented the EU-PACT strategy, the 3-day initial dose would have been 4.8 mg greater among participants randomized to pharmacogenetic-guided dosing, but only 2.5 mg greater among participants randomized to clinically guided dosing ( P <0.001). Conclusion: Compared with the COAG trial, the EU-PACT trial used systematically larger loading doses in the pharmacogenetic-guided group and might have inadequately adjusted for clinical variability in warfarin dose requirements in the fixed-dose group. Abstract : Supplemental Digital Content is available in the text.